A Study of Adhesion in Foamed WMA Binder-Aggregate Systems Using Boiling Water Stripping Tests - Anna Chomicz-Kowalska (MDPI AG, 2021)
The paper investigates the phenomena of adhesion in binder-aggregate systems produced to reflect warm-mix asphalt with water-foamed bitumen. The investigated materials included limestone and quartzite aggregates and a total of four asphalt binders: 50/70 and 45/80–55 bituminous binders obtained from two sources. The adhesive bonding between the asphalt binders and aggregates was evaluated in boiling water stripping tests, which results were quantified using digital image analysis. The bituminous binders were additionally tested for their dynamic viscosities, and their chemical composition was probed using FTIR spectroscopy. The tests were carried out using traditional liquid and foamed bituminous binders on samples prepared at temperatures characteristic of hot-mix asphalt and warm-mix asphalt production (20 °C decrease). The use of foamed binders yielded higher values of residual asphalt binder coverage of the aggregates. Limestone aggregates provided superior adhesion, with the lowest result amounting to approximately 88%, while with quartzite aggregates, the results ranged from approximately 40% to 87%. The refinery from which the asphalt binders were sourced had a significant influence on the results; however, the additional rheological and chemical analyses were insufficient to explain those differences. It was concluded that the process of asphalt binder foaming, per se, may have a beneficial impact on the resistance of the asphalt binder-aggregate system to the action of water.